Type XVII collagen interacts with the aPKC‐PAR complex and maintains epidermal cell polarity. Issue 1 (6th October 2020) - Watanabe, Mika; Kosumi, Hideyuki; Osada, Shin‐Ichi; Takashima, Shota; Wang, Yunan; Nishie, Wataru; Oikawa, Tsukasa; Hirose, Tomonori; Shimizu, Hiroshi; Natsuga, Ken
Abstract: Type XVII collagen (COL17) is a transmembrane protein expressed in the basal epidermis. COL17 serves as a niche for epidermal stem cells, and although its reduction has been implicated in altering cell polarity and ageing of the epidermis, it is unknown how COL17 affects epidermal cell polarity. Here, we uncovered COL17 as a binding partner of the aPKC‐PAR complex, which is a key regulating factor of cell polarity. Immunoprecipitation‐immunoblot assay and protein‐protein binding assay revealed that COL17 interacts with aPKC and PAR3. COL17 deficiency or epidermis‐specific aPKCλ deletion destabilized PAR3 distribution in the epidermis, while aPKCζ knockout did not. Asymmetrical cell division was pronounced in COL17‐null neonatal paw epidermis. These results show that COL17 is pivotal for maintaining epidermal cell polarity. Our study highlights the previously unrecognized role of COL17 in the basal keratinocytes.